(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Teachers rely heavily upon text books as the main instructional resource to teach German as a Foreign Language (GFL) throughout India. Communicative textbooks are developed based on the communicative language teaching approach and implement the Common European Framework of Reference (CEFR) levels. Such books include lists of communicative functions, grammar forms and language skills to be practiced by the learner simulating real-life situations in the target country. Learning a language is not only learning the alphabets, grammar or functions it’s also about learning the society, its customs and the other auxiliary communication techniques. However, it is seen that little attention has been given in textbooks in incorporating sufficient cultural content and there is an imbalance in the way both surface and deep culture are dealt in textbooks. This study therefore investigates the representation of surface and deep culture in an A1 level German textbook “NETZWERK”. Analyzing the cultural content represented in the textbook reveals that there is a discernible gap in the way surface and deep cultures are dealt with in the textbook. Nevertheless the additional tools incorporated in the course book if used effectively in the GFL classroom would enhance the learning of deep culture and fortify the intercultural competency of the learners.